Ответы и объяснения

Лучший Ответ!
  • Yena
  • главный мозг
2013-04-23T19:18:58+00:00

x^3 + 3x^2 - 9x - 27 = 0\\\ x^2(x+3)-9(x+3)=0\\\ (x+3)(x^2-9)=0\\\ (x+3)(x+3)(x-3)=0\\\ (x+3)^2(x-3)=0\\\

x+3=0     или     x-3=0

  x=-3                    x=3

2013-04-23T19:21:02+00:00

ответ во влажении!

###########################################################################################################################################################################################################################################################################################################################################################################################################################################################